The eight masks of men - Grosse, Frederick G.
1 online resource (154 pages).
Keywords: In today's rapidly changing society, the rules you learned as a child may no longer apply, causing you to experience restlessness and confusion. The Eight Masks of Men: A Practical Guide in Spiritual Growth for Men of the Christian Faith will encourage you to come out from behind your mask of solitude and loneliness--one of man's most obtrusive masks--and reach out for help and community. By answering questions commonly asked by men of various religious and personal backgrounds, this book will help you tune into your feelings, innermost thoughts, and that void you feel inside. As you become consciously aware of how the eight masks are a part of your being, you will recognize the true gift beneath each one. The Eight Masks of Men is the first book to combine historical, theological, and sociological perspectives with a practical approach for personal growth. To help you divest yourself of your inhibitions and experience inner harmony, it blends personal stories, humorous anecdotes, biblical research, and clinical information. The eight masks that men wear and what they hide that author Rev. Dr. Frederick G. Grosse explores include: mask: loneliness; hides: desire for community mask: rage and anger; hide: pain and hurt mask: compulsion; hides: desire for love mask: performance; hides: desire for acceptance mask: control; hides: desire for friendship mask: producing; hides: desire to just "be" mask: competition; hides: desire for humility mask: institutional religion; hides: desire for spiritual growthDon't let tragedy or desperation strike before you commit to building a healthier relationship with yourself, the people important to you, and God. Men who feel out of touch with their spiritual sides, retreat and spiritual direction leaders, pastoral counselors, chaplains, marriage and family counselors, and members of the clergy will find in The Eight Masks of Men the inspiration and insight they need to guide themselves and one another to a season of union with God.